Analisis Faktor-Faktor Yang Mempengaruhi Produktivitas Padi Sawah Di Kelurahan Anduring Kecamatan Kuranji Kota Padang (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2025)
This research aims to analyze the factors Affecting the productivity of lowland rice in Anduring Village. This research was using survey methods on sample of 30 peoples through simple random sampling. This research was conducted during the growing season period January-April 2016. Data analysis used the Cobb-Douglas production function with the OLS (Ordinary Least Square) methods. The research results show that the research shows that the factors that have a significant influence on lowland rice productivity in Anduring Village are urea fertilizer with a coefficient value of 30.077, while the variables of land area and pesticide use have a positive but not significant effect with coefficient values ​​of 98.12 and 25.26. Farmers should pay more attention to using fertilizer doses and pesticide doses properly in accordance with the recommendations set by the Ministry of Agriculture.